Morphological characteristics of forage crops indigofera zellongeriana at different levels drought stress and interval pruning - Herdiawan, Iwan; Abdullah, L; Sopandie, D; Karti, P.D.M.H; Hidayati, N (Indonesian Journal of Animal and Veterinary Sciences, 2012)
The objectives of this experiment was to evaluate the effect of drought stress and defoliation interval on shoot and root morphologic characteristic of Indigofera zollingeriana. The experiment was arranged in a completely randomized design with two factors and four replications. The first factor consisted of 3 level of drought stress i.e: 100% field capacity (FC) (control), 50% FC, and 25% FC. The second factor comprised of 3 defoliation interval were interval defoliations of 60, 90 and 120 days. The observed variables were shoot, root dry weight, root/shoot ratio and root length. Data were analyzed by ANOVA and the differences between treatments were tested by LSD. The results shows that there were interactions (P < 0,05) between drought stress and defoliations interval on shoot dry weight, while root dry weight, root/shoot ratio, and root length was not. Drought treatment significantly (P < 0,05) decreased shoot, root dry weight, but increase of root/shoot ratio and root length. Defoliation interval significantly affected (P < 0,05) on shoot dry weight, but not on root dry weight, root/shoot ratio, and root length. Key Words: Indigofera zollingeriana, Drought Stress, Defoliation Interval, Shoot And Root Morphology